2017
DOI: 10.1111/cdoe.12344
|View full text |Cite
|
Sign up to set email alerts
|

Rural‐urban disparity in oral health‐related quality of life

Abstract: The results of this study suggest a potential difference in OHRQoL of Quebec rural and urban populations, and a need to develop strategies to promote oral health outcomes, specifically for rural residents. Further studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 52 publications
2
42
0
3
Order By: Relevance
“…Our study also showed that students who lived in rural places during childhood had higher odds of reporting low OHRQoL compared to those who lived in urban places. Geographical remoteness, socioeconomic deprivation, and limited access to OH services have been discussed by other researchers to explain these differences [ 30 ]. Indeed, the European North-West of Russia has a low population density, covering an area of approximately 1.5 million km 2 , but with a population of only 4.6 million (78.9% urban in 2016) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that students who lived in rural places during childhood had higher odds of reporting low OHRQoL compared to those who lived in urban places. Geographical remoteness, socioeconomic deprivation, and limited access to OH services have been discussed by other researchers to explain these differences [ 30 ]. Indeed, the European North-West of Russia has a low population density, covering an area of approximately 1.5 million km 2 , but with a population of only 4.6 million (78.9% urban in 2016) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that persons living in socially deprived communities, such as rural areas, have less access to health services and poorer health status than those from betteroff communities [2,3]. Rural populations may also experience poorer oral health and limited access to dental care [4][5][6][7]. The rate of dental attendance by people living in rural areas is lower and they are more likely to postpone dental appointments due to financial restrictions [8].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this health inequality, it is necessary to urge the local community to make the most of existing resources. In rural areas, there is less opportunity to participate in health education programs than in urban areas 35,37,39 . Therefore, there is a need to improve the benefits of health education through more effective interventions in rural areas.…”
Section: Discussionmentioning
confidence: 99%